2013
DOI: 10.4314/bcse.v27i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride levels in commercially available rice in Ethiopia

Abstract: ABSTRACT. Rice (Oryza sativa, Asian; Oryza glaberrima, African) is an important staple food crop in many Sub-Saharan African and Asian countries, so the consumer's daily bowl of rice needs to be safe and of good quality. The objective of this study was to determine level of fluoride in raw and cooked rice by ion selective electrode. Alkaline fusion was used for sample preparation of six varieties for both the raw rice and rice cooked with tap water and fluoridated water. Fluoride levels ranged from 0.1-5.5 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 22 publications
4
19
1
Order By: Relevance
“…Analysis of raw Chinese rice showed a relationship between minerals which can be represented as Zn > Mn > Cu > Fe [ 50 ]. In turn, for Ethiopian rice, it was Fe > Zn > Cu > Mn [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of raw Chinese rice showed a relationship between minerals which can be represented as Zn > Mn > Cu > Fe [ 50 ]. In turn, for Ethiopian rice, it was Fe > Zn > Cu > Mn [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…0.3-0.46 g K, 0.19-0.36 g Mg and 0.09-0.16 g Ca per 1 kg. Cooked Ethiopian rice contained K (1.01 g kg −1 dry weight) > Ca (0.24 g kg −1 dry weight) > Mg (0.13 g kg −1 dry weight) [18]. However, studies carried out by Rybicka et al [19] revealed that some gluten-free breads (with a significant share of corn flour) contained K > Ca > Mg, which is difficult to explain as corn flour, like other types of flour, contains more Mg than Ca.…”
Section: Discussionmentioning
confidence: 99%
“…The total exposure of fluoride depends on the contributions from various sources, such as drinking water, water-based beverages, foods, food supplements, toothpaste, and air [17][18][19][20][21][22][23][24][25]. Which means foods, beverages, carbonated soft drinks, and dental products are considered as the main sources of fluoride intake for children above one years of age [6].…”
Section: Introductionmentioning
confidence: 99%
“…Food sources contain various concentrations of fluoride and are the largest contributor to fluoride exposure [17][18][19][20][21][22][23][24][25]. Soft drinks contribute the fluoride intake by the people who regularly consume Coca Cola, Pepsi, Mirinda, Fanta and Sprite [6,29,30].…”
Section: Introductionmentioning
confidence: 99%